PERANAN KOMUNIKASI KELUARGA DALAM PERSPEKTIF ISLAM - Helmanda, Cut Mawar; Pratiwi, Novita (Jurnal Dakwah Tabligh, 2018)
Communication plays the most important role in a family. Due to family is the smallest unit in society, it influences the family members to have good values in communication to be implemented in society, later. Furthermore, Islam has its own perpective on communication. It guides the family to interact among the siblings and so forth. Islam shows the principles that should be obeyed to create comfort life.